2021
DOI: 10.31234/osf.io/dnc87
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual and Gender Minorities Facing the Coronavirus Pandemic: A Systematic Review of the Distinctive Psychosocial and Health-related Impact

Abstract: Sexual and gender minorities (SGM) constitute vulnerable groups in many countries. Thus, they might be affected to a different extent than heterosexual and cisgender individuals by the Coronavirus pandemic. The aim of this systematic review is to summarize the current state of international research on the effects of the Coronavirus pandemic on SGM individuals. Following the PRISMA protocol, we synthesized 35 publications including different article formats. Key findings yield that SGM individuals overall suff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…32 However, this population also experiences discrimination and stress at baseline and may have been disproportionately impacted by the stressors of the pandemic. Given that only one third of transgender youth live in home with family acceptance, 33,34 the extended school closures in Oregon may have been a particular challenge for these youth, in addition to increased barriers to transgender care.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, this population also experiences discrimination and stress at baseline and may have been disproportionately impacted by the stressors of the pandemic. Given that only one third of transgender youth live in home with family acceptance, 33,34 the extended school closures in Oregon may have been a particular challenge for these youth, in addition to increased barriers to transgender care.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Brazil in 2020 found that 7.9% of MSM and transgender participants to report low psychological well-being (9), whereas research conducted in Mexico suggested high levels of depression among MSM and transgender women during the COVID-19 pandemic when compared to before the pandemic (10). A systematic review from available evidence revealed that overall MSM and transgender individuals suffered from disproportionate negative influence of stressors linked to the pandemic due to preexisting vulnerabilities (11). The findings also suggested MSM and transgender peoples vulnerability were increased by mental health, economic deficit, and physical vulnerability during the pandemic (11).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review from available evidence revealed that overall MSM and transgender individuals suffered from disproportionate negative influence of stressors linked to the pandemic due to preexisting vulnerabilities (11). The findings also suggested MSM and transgender peoples vulnerability were increased by mental health, economic deficit, and physical vulnerability during the pandemic (11). To the best of our knowledge, there was no literature available specifically focusing on happiness amongst MSM and transgender people during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%